2020
DOI: 10.1515/ijsl-2020-2113
|View full text |Cite
|
Sign up to set email alerts
|

Language use and attitudes toward Kaqchikel and Spanish in San Marcos La Laguna, Guatemala

Abstract: This study focuses on the factors contributing to language maintenance and shift in the bilingual community of San Marcos La Laguna, Guatemala, where both Spanish and Kaqchikel are spoken. For many decades, San Marcos was relatively isolated from other nearby communities and many speakers were monolingual in Kaqchikel. However, recent changes in the community, particularly a rise in tourism and access to education, have contributed to an increased need for Spanish. The present study draws from qualitative data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In her study of the heavily indigenous community of Comalapa, located some 25 km higher in the highlands from Parramos, Garzon (1998) describes a situation in the late 1980s in which bilingualism had spread considerably in comparison to that described by Farber (1978) for the same community. Most recently, Jandrey Hertel and Barnes (2020) examine subjects’ statements about use and attitudes toward Kaqchikel and Spanish in San Marcos La Laguna, on the shore of Lake Atitlán . They highlight attitudes assigning Spanish value for commerce and education, in contrast to ascriptions of value to Kaqchikel for ethnic identity and social cohesion.…”
Section: Studies Of Kaqchikel Maya and Spanish Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…In her study of the heavily indigenous community of Comalapa, located some 25 km higher in the highlands from Parramos, Garzon (1998) describes a situation in the late 1980s in which bilingualism had spread considerably in comparison to that described by Farber (1978) for the same community. Most recently, Jandrey Hertel and Barnes (2020) examine subjects’ statements about use and attitudes toward Kaqchikel and Spanish in San Marcos La Laguna, on the shore of Lake Atitlán . They highlight attitudes assigning Spanish value for commerce and education, in contrast to ascriptions of value to Kaqchikel for ethnic identity and social cohesion.…”
Section: Studies Of Kaqchikel Maya and Spanish Contactmentioning
confidence: 99%
“…Scholars, including Carroll (1962), Gardner (1985), and Dörnyei and Ushioda (2009), have suggested that attitude is one of the most important variables in predicting ability in a learned language. Scholars, including Becker Richards (1998), French (2002), Maxwell (2009), and Jandrey Hertel and Barnes (2020), have also recognized the role of attitudes in publications focusing on the Kaqchikel region . Here, two types of attitudes will be examined.…”
Section: Attitudes Domains and Acquisitionmentioning
confidence: 99%